Echocardiographic evaluation of cardiac diastolic function in patients with rheumatoid arthritis: 5 years of follow-up - FAK, ALİ SERDAR; DİRESKENELİ, RAFİ HANER; TOKAY TARHAN, SENA (SPRINGER LONDON LTD, 2008)
Rheumatoid arthritis (RA) is associated with increased cardiovascular mortality. However, cardiovascular findings are mostly subtle, and diastolic function abnormalities are one of the earliest manifestations. The aim of this study was to determine diastolic function abnormalities in RA patients and to make a reevaluation of diastolic function after 5 years of follow-up. Seventy-two RA patients (mean age: 48+/-11 years, F/M: 62/10) without any known cardiac disease and 67 controls (mean age: 46+/-11 years; F/M: 53/14) were recruited. Disease activity score (DAS), lipid values, and C-reactive protein (CRP) levels were determined. Left ventricular mass, isovolumetric relaxation time, mitral annular early (E), and late (A) diastolic filling rate were determined by M-mode two-dimensional color Doppler echocardiography. Mitral annular early (E') and late (A') diastolic velocities were also evaluated by tissue Doppler echocardiography. Twenty-four RA patients were reevaluated after 5 years of follow-up with DAS, biochemical variables, and echocardiography. Fifty five of 72 (76%) RA patients and 12 of the 67 (18%) controls had diastolic dysfunction (DD). Seven of ten patients with DD at baseline continued to have DD, whereas three did not show DD at 5 years. Six of 14 patients without DD at baseline developed DD at follow-up, while eight patients sustained normal diastolic function. Although DAS and lipid values were not altered during the course of 5 years, CRP levels decreased significantly (P<0.05). In conclusion, RA patients have diastolic function abnormalities compared to healthy controls. Five-year follow-up of a subgroup of our patients showed that, although clinical response was unsatisfactory, cardiac function was conserved without a major deterioration. Moreover, DMARDs, such as anti-TNF alpha agents, do not seem to have a major adverse effect on cardiac findings in these patients.
Keywords: cardiac involvement; diastolic function; rheumatoid arthritis; TISSUE DOPPLER; MORTALITY